IMPROVING THE EFFICIENCY OF FOREIGN ECONOMIC ACTIVITY OF ENTERPRISES ON THE BASIS OF MARKET RESEARCH - Iryna Gontareva; Mariia Nesen (Соціальна економіка)
The article is aimed at studying the status and trends in the development of foreign economic activity in Ukraine and in the world, and the impact of marketing research on their efficiency. The purpose of the study is to analyze the improvement of the efficiency of foreign economic activity of enterprises on the basis of marketing research using economic and statistical methods, to identify problems and prospects for development, and to develop ways for effective foreign economic activity in conducting marketing research. The article provides data on the volume of the marketing data market worldwide as of 2017-2021, the results of a survey of European companies on the benefits received after investing in sustainable marketing strategies as of July 2022.